2018
DOI: 10.3389/fpubh.2018.00210
|View full text |Cite
|
Sign up to set email alerts
|

Live Poultry Trading Drives China's H7N9 Viral Evolution and Geographical Network Propagation

Abstract: The on-going reassortment, human-adapted mutations, and spillover events of novel A(H7N9) avian influenza viruses pose a significant challenge to public health in China and globally. However, our understanding of the factors that disseminate the viruses and drive their geographic distributions is limited. We applied phylogenic analysis to examine the inter-subtype interactions between H7N9 viruses and the closest H9N2 lineages in China during 2010–2014. We reconstructed and compared the inter-provincial live p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Considering evidence that H5N1 and H7N9 viruses were likely associated with the live poultry trade ( Bui et al. 2018 ; Li et al. 2018 ; Yang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering evidence that H5N1 and H7N9 viruses were likely associated with the live poultry trade ( Bui et al. 2018 ; Li et al. 2018 ; Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ), in this study, based on the phylogeographic approach, we found that H5N6 viruses from Guangdong and Hunan provinces were more likely to have originated from, and migrated to, at least eleven locations and four locations, respectively, which implies that H5N6 viruses endemic in southern China might have jointly resulted from the gene flow through circular poultry movements. Livestock breeding is extensive in southern China, with many breeding poultry farms, particularly “free range” ducks that are raised in large amount of small backyard farms, and live poultry markets ( Li et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, farmers and local authorities were reluctant to report avian influenza outbreaks, in particular, the asymptomatic LPAI virus H7N9 cases. Some farmers and small companies even transported infected poultry away from their premises once a viral infection had been identified, further facilitating the spread of the virus [49]. The difficulties associated with monitoring/preventing short distance, live poultry transportations potentially contributed to the repeated waves of H7N9 influenza virus outbreaks in China.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates from the western Chinese provinces clustered with isolates from various districts, while most of the isolates showed the highest homology with isolates from the neighboring provinces. This indicates that the majority of H7N9 viruses in the newly affected western Chinese provinces might have been imported from the neighboring provinces, most possibly by live poultry or poultry product transport, which has been shown to be a driver of China's H7N9 viral evolution and geographical network propagation (Gao, 2014;Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%